Super-refractory status epilepticus and pharmacoresistant epilepsy in an infant with hemorrhagic shock and encephalopathy syndrome - Kravljanac Ružica (Srpski Arhiv za Celokupno Lekarstvo, 2021)
Introduction. Hemorrhagic shock and encephalopathy syndrome (HSES) is a rare disorder with prevalence at an early age. The main features of HSES are acute diarrhea, shock, disseminated intravascular coagulation, multisystem impairment, and encephalopathy. The prognosis is very poor, with high mortality, especially in cases with status epilepticus. Case outline. The presented infant had typical features of HSES associated with super-refractory status epilepticus as de novo epileptic event, followed by pharmacoresistant epilepsy. Clinical course of the disease was very severe and required urgent circulatory and respiratory support, and simultaneous management of super-refractory status epilepticus by continuous intravenous infusion of midazolam, barbiturate, and levetiracetam. The outcome was very poor with serious neurological consequence and resistant epileptic seizures. Conclusion. The treatment of the presented patient with HSES was very challenging due to a lifethreatening condition associated with super-refractory status epilepticus, and further pharmacoresistant epilepsy. Additionally, the choice of antiepileptic drugs is limited due to multisystem impairment and adverse effects which might worsen the already severe course of the disease.